Conversations on the Global South - The South on the South: Interview with Raewyn Connell - Claudio, Lisandro E. (Archīum Ateneo, 2013)
In the first of a series of conversations about the Global South, Social Transformations: Journal of the Global South editors Lisandro E. Claudio and Karl Cheng Chua (STJGS) speak to Raewyn Connell (RC) about the generating conversations about the Global South in the Global South.